جوليان ستيوارد ومعاينة الايكولوجيا: بحث في الانثروبولوجيا الثقافية - العباسى، ياس خضر عباس (الجامعة المستنصرية - كلية الآداب, 2015)
J. Steward rose as one of the disciples of the American Anthropological school on the study of culture and human behavior and its interpretation in the misfortunes of the last century after a series of studies in archeology and anthropology, has been allocated the fifth and sixth decade toward anthropological studies through orientation cultural ecology, which means the adaptation of humans to the environment, try the research to look to know the biography of academic and scientific career and achievements of knowledge of Professor (Steward), as the goal, while moving the importance about the discussion and the statement of the most important ideas and concepts presented in the studies and their ability to analyze human behavior as filled cultural anthropology basis, and in his discussion to the evolutionary school classic concept of linear evolution stages by the pioneers of this school, as well as his discussion to the theoretical orientations given by the follow geographical or environmental determine in identifying and formulating taxable environmental determinants of human behavior, and the extent of the contribution of the cultural ecology widening the search rather than specified in the specific scenarios.
بزغ الأستاذ (j. Steward) كأحد تلاميذ المدرسة الأنثروبولوجية الأمريكية المعنية بدراسة الثقافة والسلوك الإنساني وتفسيره في منتصف الأربعينيات من القرن الماضي بعد سلسلة من الدراسات في علم الآثار والانثروبولوجيا، وقد خصص العقد الخامس والسادس نحو الدراسات الأنثروبولوجية من خلال توجه الايكولوجيا الثقافية الذي يعنى بتكيف البشر إلى البيئة، يحاول البحث أن يعرف بالسيرة الأكاديمية للأستاذ (Steward) ومسيرته العلمية وإنجازاته المعرفية، بوصفها هدفا للبحث، في حين تتجه الأهمية نحو مناقشة وبيان أهم الأفكار والتصورات التي عرضها في دراساته وقدرتها في تحليل السلوك الإنساني بوصفه شغل الانثروبولوجيا الثقافية الأساس، وفي مناقشة توجهات المدرسة التطورية الكلاسيكية ومفهوم التطور الخطي الذي رسمه رواد هذه المدرسة، فضلا عن مناقشة التوجهات النظرية التي قدمها أتباع الحتمية الجغرافية أو البيئية في تحديد وصياغة السلوك الإنساني الخاضع للمحددات البيئية، ومدى مساهمة الايكولوجيا الثقافية توسيع دائرة البحث بدل من تحديده في تصورات محددة..
Keywords: ستيوارد -- الايكولوجيا الثقافية -- البيئة -- الانثروبولوجيا الثقافية